2008
DOI: 10.5194/tc-2-109-2008
|View full text |Cite
|
Sign up to set email alerts
|

Snow melting bias in microwave mapping of Antarctic snow accumulation

Abstract: Abstract. Satellite records of microwave surface emission have been used to interpolate in-situ observations of Antarctic surface mass balance (SMB) and build continental-scale maps of accumulation. Using a carefully screened subset of SMB measurements in the 90 • -180 • E sector, we show a reasonable agreement with microwave-based accumulation map in the dry-snow regions, but large discrepancies in the coastal regions where melt occurs during summer. Using an emission microwave model, we explain the failure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Even though the L-band radiation emanates from deep in the ice sheet, surface reflection is an important process of the radiative transfer. It has been demonstrated that regions where melt occurs can bias snow accumulation retrievals using microwave TB (Magand et al, 2008), Fig. 4 shows that similar bias can be expected using L-band observations.…”
Section: The Greenland Ice Sheet (Gis)mentioning
confidence: 49%
“…Even though the L-band radiation emanates from deep in the ice sheet, surface reflection is an important process of the radiative transfer. It has been demonstrated that regions where melt occurs can bias snow accumulation retrievals using microwave TB (Magand et al, 2008), Fig. 4 shows that similar bias can be expected using L-band observations.…”
Section: The Greenland Ice Sheet (Gis)mentioning
confidence: 49%
“…Furthermore, Magand et al . [] show that regions potentially affected by melting should be completely masked‐out from the microwave‐based interpolation schemes. It is clear that surface melting occurs on FIS in the present climate [ Schlosser et al ., ; Kaczmarska et al ., ], which may be responsible for the large discrepancies between our results and those of Arthern et al .…”
Section: Spatiotemporal Patterns Of Surface Mass Balancementioning
confidence: 99%
“…Glazed surfaces (Frezzotti et al, 2002a;Scambos et al, 2012), thermal cracks and irregular patches of hoar on the surface (Gow, 1969;Courville et al, 2007) can also be found at some specific points. These features affect the distribution of snow accumulation and represent one of the challenges in scaling up local surface mass balance measurements to the continent scale (Goodwin, 1990;Magand et al, 2008;Das et al, 2013). Although the size of these features is much smaller than the microwave radiometer footprint, they have an influence on the signal.…”
Section: Introductionmentioning
confidence: 99%